2018
DOI: 10.1557/adv.2018.327
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary Multidewetting of Thin Films

Abstract: Thermocapillary dewetting of liquids and molten films has recently emerged as a viable alternative to conventional microprocessing methods. As this thermal gradient-induced mechanism is universal, it can be applied to any material. This work explores the sequential dewetting of materials with varying melting points, including polymers and metals, to create aligned morphologies. The variation in melting point allows for the dewetting of single layers at a time or mobility-limited simultaneous dewetting. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Through local softening, samples that are solid both before and after excitation lock in the effects of the exposure, such as dewetting 22 25 and/or zone annealing 26 28 . We have also shown that FLaSk has the ability to selectively pattern multilayers of material 29 . For the purposes of templating, FLaSk is developer-free and grayscale allowing for partial to complete dewetting in submicron feature sizes followed by immediate spray.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Through local softening, samples that are solid both before and after excitation lock in the effects of the exposure, such as dewetting 22 25 and/or zone annealing 26 28 . We have also shown that FLaSk has the ability to selectively pattern multilayers of material 29 . For the purposes of templating, FLaSk is developer-free and grayscale allowing for partial to complete dewetting in submicron feature sizes followed by immediate spray.…”
Section: Introductionmentioning
confidence: 72%
“…The microhole array on PS thin films was prepared by FLaSk dewetting as described previously 29 . Briefly, we sputtered a 35 nm gold film onto a 1-mm thick glass substrate using an Anatech Ltd Hummer X gold sputter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This temperaturedependent patterning allows us to forego traditional lithographic patterning and etching techniques to pattern surfaces. Additionally, patterns formed via FLaSk dewetting are not limited to the masks used in conventional photolithography; translation of the laser stage and direct manipulation of laser parameters such as power and spot size allow precise control of 2D template size, with individual feature resolutions as small as 1.35 μm 22 . The size of the dewetted pattern has been determined to be dependent only on laser power and material molecular weight 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patterns formed via FLaSk dewetting are not limited to the masks used in conventional photolithography; translation of the laser stage and direct manipulation of laser parameters such as power and spot size allow precise control of 2D template size, with individual feature resolutions as small as 1.35 μm 22 . The size of the dewetted pattern has been determined to be dependent only on laser power and material molecular weight 22,23 . FLaSk is also compatible with low Tg materials, meaning that the templating process can be performed at low temperatures.…”
Section: Introductionmentioning
confidence: 99%